Hybrid governance, organisations and society value creation perspectives - Johanson, Jan-Erik; Vakkuri, Jarmo (Routledge, Taylor & Francis Group, 2021)
The era of hybrid governance is here. More and more organizations occupy a position between public and private ownership. And value is created not through business or public interests alone, but through distinct forms of hybrid governance. National governments are looking to transform their administrative systems to become more business driven. Likewise, private enterprises are seeing value gains in promoting public interest in their corporate social responsibility programs.